2002
DOI: 10.1142/s0218625x02003986
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Properties of Two Isolated Steps: A Theoretical Model

Abstract: We investigate the dynamical properties of two isolated steps on the surface. We present the solution of the full dynamical problem arising from the absence of translation symmetry in two dimensions due to extended surface steps on the surface boundary of an insulating substrate. The calculations concern in particular the dynamics of localized modes of an atomic step on the surface of a cubic lattice. The theoretical approach determines the vibrational field in both steps. The matching method, which constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…15 The experimental evidence that demonstrates the localized phonons on the step edges of vicinal Ni (977) surface was observed using helium-atom scattering 16 and was addressed by Niu et al 17 Recently, we have theoretically treated the dynamical properties of quasi-low-dimensional structure consisting of two monoatomic steps at the interface between three coupled semi-infinite and single semi-infinite atomic layers. 18 Results of which were in qualitative agreement with previous works [19][20][21] and demonstrated that the breakdown of translational symmetry normal to the step edges give rise to several branches parallel to them.…”
Section: Introductionsupporting
confidence: 89%
“…15 The experimental evidence that demonstrates the localized phonons on the step edges of vicinal Ni (977) surface was observed using helium-atom scattering 16 and was addressed by Niu et al 17 Recently, we have theoretically treated the dynamical properties of quasi-low-dimensional structure consisting of two monoatomic steps at the interface between three coupled semi-infinite and single semi-infinite atomic layers. 18 Results of which were in qualitative agreement with previous works [19][20][21] and demonstrated that the breakdown of translational symmetry normal to the step edges give rise to several branches parallel to them.…”
Section: Introductionsupporting
confidence: 89%
“…For surface with inhomogeneities such as two isolated steps, the problem has been recently addressed. 24 The breakdown of translational symmetry perpendicular to the steps edges gives rise to several Rayleigh-like branches localized in the neighborhood of the steps. We apply this procedure for the two-dimensional systems in the neighborhood of inhomogeneity, such as an interface extending from the boundary into the right and left domains of a perfect waveguide, in order to derive a unique solution for the commensurate evanescence of localized vibrational states in two dimensions near the interface.…”
Section: Dynamics Of Phonon Scattering By An Interfacementioning
confidence: 99%